Teaching in the University Learning from Graduate Students and Early Career Faculty - Westfall-Rudd, Donna; Vengrin, Courtney; Elliott-Engel, Jeremy (Open textbook library., 2022)
The primary objective of this book is to provide a resource for graduate teaching assistants who are looking for practical strategies and guidance as they begin their careers as postsecondary STEM educators. The text is designed to address a comprehensive list of topics to support the professional development of new faculty, recognizing that those holding academic faculty positions within a college or university are expected to be active in teaching, discovery, and outreach. Traditional doctoral education programs have historically emphasized preparation for research and scholarly publications, and for outreach. However, to some extent, many candidates who complete doctoral programs have minimal preparation and training in formal teaching. Contributors to this text have had a unique experience as part of a three-year, college-wide program designed to prepare interested doctoral students for a rewarding academic career. The program is designed to support the professional development of new faculty, recognizing that those holding academic faculty positions within a college or university are expected to be active in teaching, discovery, and outreach. The alumni and scholars of the program have worked collectively to gather resources and implement educational practices in the diverse set of courses they taught in during their three years in the program. Now as new faculty at a variety of postsecondary institutions across the United States, these early-career educators bring their insights and real-world teaching experiences, embedded in contemporary teaching and learning theory to their contributions to this text. What is this resource? This text is a collection of chapters and vignettes intended to provide practical insight into the challenges and opportunities of teaching at the postsecondary level. It is anticipated that the vignettes provide examples of contexts in which the principles of the topic chapters are applied. Goals for this book Support future STEM faculty in their efforts to engage in student-centered teaching practices that create inclusive postsecondary classrooms Support improved the preparation of new faculty to engage in community education and outreach as part of their professional responsibilities. Support graduate students preparing to apply and interview for faculty positions with teaching appointments. If you are an instructor reviewing, adopting, or adapting this textbook, please help us understand your use by filling out this form http://bit.ly/teaching-interest.